Nova família de inversores multiníveis assimétricos com estágio CA-CA e com reduzido número de componentes em condução - Mesquita, Samuel Jó de (2016)
This thesis proposes a new family of asymmetric multilevel inverters based on the use of bi-directional switches. Generalized voltage relations among input sources of the cascaded inverters are developed and comparative analyzes with conventional topologies show an attractive solution in relation to the reduction of the number of components in conduction, as well as the reduced number of isolated DC sources. Topological solutions employing only one DC source are presented and the AC-AC operating stage of these converters does not require diode bridges to create the power supplies of asymmetric multilevel inverters as commonly proposed by the scientific community. PWM modulation strategies for some topologies are proposed and validated by simulation results. Among the proposed topologies, two topologies of higher complexity were chosen to validate the studies by means of a 49-level output voltage laboratory prototype, using a toroidal transformer with multiple secondary windings, being one topology operating at 300 Hz, and the second one at 60 Hz. Experimental results for the two topologies processing 1 kW with 48 V input voltage and 220 V output validate these converters as well as the optimized commutation states of the bi-directional switches. In this way, this work introduces new multilevel inverter topologies viable for low power and low voltage operation.